Upaya meningkatkan kreativitas pada konten dalam meningkatkan kesadaran masyarakat untuk melestarikan lingkungan di Ditjen PPKL KLHK - Monica Alycia Mutiara; Anisatul Auliya (Journal of Environment and Geography Education, 2024)
Background: Communication is the most important thing in people's daily lives, including within the scope of government agencies. Findings: Therefore, through the final work, the author will discuss the role of a social media specialist in managing and increasing the creativity of the Directorate General of PPKL (Pengendalian Pencemaran dan Kerusakan Lingkungan)'s social media so that it can increase engagement and provide awareness to the public. Methods: Writing Akir's Assignment is supported by observations, literature studies, and interviews to get the answer that a Social Media Specialist has an important role in managing social media, especially within the scope of government agencies. Conclusion: Thus, the author comes to the conclusion that through invitation content developed through creativity in content it can attract the interest of more people.